Distinctive molecular signature and activated signaling pathways in aortic smooth muscle cells of patients with myocardial infarction. (April 2018) - Wongsurawat, Thidathip; Woo, Chin Cheng; Giannakakis, Antonis; Lin, Xiao Yun; Cheow, Esther Sok Hwee; Lee, Chuen Neng; Richards, Mark; Sze, Siu Kwan; Nookaew, Intawat; Kuznetsov, Vladimir A.; Sorokin, Vitaly
Abstract: Background and aims: We aim to identify significant transcriptome alterations of vascular smooth muscle cells (VSMCs) in the aortic wall of myocardial infarction (MI) patients. Providing a robust transcriptomic signature, we aim to highlight the most likely aberrant pathway(s) in MI VSMCs. Methods and results: Laser-captured microdissection (LCM) was used to obtain VSMCs from aortic wall tissues harvested during coronary artery bypass surgery. Microarray gene analysis was applied to analyse VSMCs from 17 MI and 19 non-MI patients. Prediction Analysis of Microarray (PAM) identified 370 genes that significantly discriminated MI and non-MI samples and were enriched in genes responsible for muscle development, differentiation and phenotype regulation. Incorporation of gene ontology (GO) led to the identification of a 21-gene VSMCs-associated classifier that discriminated between MI and non-MI patients with 92% accuracy. The mass spectrometry-based iTRAQ analysis of the MI and non-MI samples revealed 94 proteins significantly differentiating these tissues. Ingenuity Pathway Analysis (IPA) of 370 genes revealed top pathways associated with hypoxia signaling in the cardiovascular system. Enrichment analysis of these proteins suggested an activation of the superoxide radical degradation pathway. An integrated transcriptome-proteome pathway analysis revealed that superoxide radical degradation pathway remained the most implicated pathway. The intersection of the top candidate molecules from the transcriptome and proteome highlighted superoxide dismutase (SOD1) overexpression. Conclusions: We provided a novel 21-gene VSMCs-associated MI classifier in reference to significant VSMCs transcriptome alterations that, in combination with proteomics data, suggests the activation of superoxide radical degradation pathway in VSMCs of MI patients. Highlights: Remote effect of myocardial infarction on aortic vascular smooth muscle cells identified in human. The gene expression profiling analysis identified a novel 21-gene classifier distinguishing VSMCs responses to MI. The systems biology demonstrated complementary transcriptomic and proteomic changes identified SOD1 activation in MI aorta. Analysis using IPA reveals hypoxia signaling in cardiovascular system as a top activated pathway in VSMCs of MI patients.